The firm-specific determinants of capital structure: an analysis into performing construction sector in Malaysia and Singapore / Siti Zulaikha Upilin - Upilin, Siti Zulaikha (2019)
This study aims to investigate the Firm-Specific Determinants of Capital Structure: An Analysis on Construction Sector in Malaysia and Singapore. This study used panel data from ten performing construction firms in Malaysia that listed in top10malaysia.com and ten performing construction firms in Singapore that listed in aspire.shareinv.com. The timeframe for data collection is from 2009 to 2018. The dependent variable in this study is capital structure proxy by leverage, meanwhile the independent variables in this study is firm size, profitability and asset tangibility. The finding on Malaysian construction firms indicates that all variable have positive but insignificant relationship with the leverage. Meanwhile, the findings on Singapore construction firms reveal that firm size has positive and significant relationship with leverage. The findings of the study suggest that the financing pattern of construction sector in Malaysia and Singapore are in line with pecking order theory, where profitable firm prefer to finance its operation and investment opportunity using retained earnings.